2017
DOI: 10.1007/s00405-017-4545-4
|View full text |Cite
|
Sign up to set email alerts
|

Tongue surgeries for pediatric obstructive sleep apnea: a systematic review and meta-analysis

Abstract: Most children undergoing tongue surgeries in the literature were syndromic and had craniofacial disorders, co-morbidities, or other serious medical issues. Children with a body mass index <25 kg/m and non-syndromic children have had the most improvement in AHI. The specific type of surgery must be tailored to the patient. Patients with co-morbidities should undergo treatment in centers that are equipped to provide appropriate perioperative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…21,27,31,33,34 A recent meta-analysis showed that the average AHI improvement for BOT reduction was 6.92 in 109 pediatric patients; it also demonstrated the greater effectiveness of BOT surgery in patients with normal weight and in nonsyndromic children. 37 In our study, more patients underwent LT, with or without MPG, than MPG alone. Few studies have examined isolated MPG outcomes for OSA improvement in children, although much is written on the theory and technique.…”
Section: Discussionmentioning
confidence: 60%
“…21,27,31,33,34 A recent meta-analysis showed that the average AHI improvement for BOT reduction was 6.92 in 109 pediatric patients; it also demonstrated the greater effectiveness of BOT surgery in patients with normal weight and in nonsyndromic children. 37 In our study, more patients underwent LT, with or without MPG, than MPG alone. Few studies have examined isolated MPG outcomes for OSA improvement in children, although much is written on the theory and technique.…”
Section: Discussionmentioning
confidence: 60%
“…In a review and meta‐analysis of isolated tongue base surgery (base of tongue reduction, n = 114), hypoglossal nerve stimulation (n = 1), and tongue suspension (n = 1) for OSA in children, Camacho et al 24 identified 70 of 114 (61%) patients who had both BMI and outcome data available. These included normal‐weight, overweight, and obese children.…”
Section: Resultsmentioning
confidence: 99%
“…The graded effects of increasing weight on surgical outcomes can best be demonstrated using data from tongue base surgery. Increasing BMI z score was associated with increasing postoperative AHI in children undergoing lingual tonsillectomy, 24 and increasing BMI weight category was associated with worse outcomes following midline posterior glossectomy, 20,24 to the point where none of the children who were obese preoperatively improved and most gained weight following surgery 20 . However, these studies had small sample sizes, thus limiting generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedures reduced the mean preoperative and postoperative AHI from 16.9 ± 12.2/h to 8.7 ± 10.6/h (by 48.5%) in all 114 patients. Nonsyndromic children and children with a BMI < 25 kg/m 2 showed the most improvement in AHI [ 49 ]. More than 90% of patients who underwent tongue-base reduction surgery had previously undergone AT.…”
Section: Surgical Proceduresmentioning
confidence: 99%